Dadirri: an Indigenous place-based research methodology. (March 2022) - Ungunmerr-Baumann, Miriam-Rose; Groom, Rachel A; Schuberg, Emma L; Atkinson, Judy; (Carlie) Atkinson, Caroline; Wallace, Ruth; Morris, Gavin
We detail an Indigenous research methodology capturing community-based truth-telling in an Aboriginal community in the Northern Territory, Australia. We present Dadirri—a deep contemplative process of listening to one another—as a research methodology and a co-developed research model from the Nauiyu community. Dadirri is applied on the Country, with the cultural custodians to which it belongs, the Ngan'gikurunggkurr people from the Daly River region, Northern Territory. Dadirri links critical theory with reflective practice and is increasingly applied in Indigenous research. Insights into the synergies between Dadirri and traditional Eurocentric methodologies along with the successes and challenges of bringing Indigenous ways of knowing and Western ways of conducting research is presented as an interwoven praxis and governance/s. We conclude that the research outcomes demonstrate the interconnectedness and relational epistemologies as a framework between Dadirri and Western methodologies in a way that transforms and reconfigures futures, participants, and researchers alike.